Evaluation of bacteriological contamination pattern of open fractures of extremities in tertiary care hospital - Jain, Sourabh; Kumar, Ashok; Chhabra, Anurag; Kumar, Krishan; Chaudhary, Kulveer (International Journal of Research in Orthopaedics, 2021)
Background: Open fractures and associated complications like infection are fairly common in developing countries due to rising incidence of high velocity trauma. Primary goal of study is to evaluate the pattern of bacteriological contamination of open fractures of extremities in tertiary care hospital. Methods: A total of 316 patients of all the age group, both the sexes with open fractures of extremities presented within 6 hours were taken in to study. 1st swab taken at the time of primary wound examination followed by 2nd culture swab on just after debridement followed by 3rd culture swab on the day of 1st aseptic dressing followed by 4th culture swab if infection continues or asepsis score is more than 20 till the duration of 4 days. Culture and sensitivity reports were collected for studying pattern of bacterial isolates and their sensitivity. Results: Infection developed in 22.5% of the patients with open fractures of extremities in whom most of bacterial infections were caused by gram-negative organisms (80.3%). Cultures on admission were positive in 41 patients, out of which 11 patients had developed infection in the final cultures but with different flora. While cultures taken at 1st aseptic dressing were found to be positive in 51 cases, out of which 31 had developed infection with prognostic value of 57%. Conclusions: We concluded that cultures obtained at 1st aseptic dressing are far more predictive than pre and post-debridement cultures in management of patients with open fractures of extremities and are important in formulating an antibiotic policy.